Evaluation of the efficiency of ionic liquids in the demulsification of oil-in-water emulsions - Wamda Faisal Elmobarak (17058024) (2021)
The production of oil in water emulsions (O/W-EMUL) is prevalent in the petroleum sector due to the presence of several stabilizers; however, O/W-EMUL is an unwanted phenomenon. Given that, this study evaluates the efficiency of three ionic liquids (ILs), two halogenide ILs (HILs-1, HILs-2), and one is non-halogenide IL (Non-HIL) as demulsifiers for the recovery of oil from O/W-EMUL at a concentration of 500 mg/L. The percentage demulsification efficiency (D%) (i.e., the percentage of oil removed from the O/W-EMUL) was examined using tube and bottle tests. The results of the bottle tests demonstrated that the halogenide ionic liquids (HILs) could achieve a higher D% in comparison to the Non-HIL. The D% achieved within 20 min of treatment with HILs-1, HILs-2, and Non-HIL was found to be ∼97.7%, 88.2%, and 85.2%, respectively. Increasing the volume of ILs (VILs), which are normally recycled, can help overcome the surfactant’s effect to achieve a D% > 95%. The demulsification mechanism is based on ion exchange between the anionic part of the ILs and the oil–surfactant interphase. Recycling the ILs can be enhanced by reestablishing the IL anion part using water-free inversed ion exchange mixed with salts. The results suggest that ILs can be an appropriate substitute for commercial demulsifiers. Though, further efforts are needed to produce non-toxic and cost-effective ILs with low viscosity. The efficiency of the demulsification process may be further enhanced when using ILs with other separation processes. The achieved results support upcoming research works that apply ILs for oil removal from O/W-EMUL. Other Information Published in: Environmental Technology & Innovation License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eti.2021.102003